Silicon in Pre-sprouted Sugarcane Seedlings Mitigates the Effects of Water Deficit After Transplanting - Teixeira, Gelza Carliane Marques [UNESP]; de Mello Prado, Renato [UNESP]; Rocha, Antonio Márcio Souza [UNESP]; dos Santos, Luiz Cláudio Nascimento [UNESP]; dos Santos Sarah, Marcilene Machado [UNESP]; Gratão, Priscila Lupino [UNESP]; Fernandes, Carolina [UNESP] (Springer Nature, 2020)
This study is aimed at assessing whether silicon (Si) can mitigate the effects caused by water stress in pre-sprouted seedlings (PSS) in sugarcane after their transplanting in the soil and what is the best form in the application if via nutrient solution or leaf spraying. The treatments were arranged in a 3 × 3 factorial scheme with silicon supply via nutrient solution (2 mmol L−1), Si via leaf application (3.4 mmol L−1), and without Si (control) and three levels of soil water retention capacity (70%, 50%, and 30%), for 30 days. In the absence of Si, the water deficit was damaging to the physiological, growth, and dry matter production variables of plants, in a 30% level of soil water retention capacity. Silicon supply via nutrient solution was more efficient when compared with Si via leaf spraying in the formation of pre-sprouted sugarcane seedlings in the first 30 days after transplanting, since it increased the quantum efficiency of photosystem II, chlorophyll content, leaf water potential, and water content, decreased cell electrolyte leakage and free proline content, and allowed a higher growth and biomass production. In conclusion, the supply of Si via nutrient solution in pre-sprouted sugarcane seedlings can be considered a feasible alternative to alleviate water deficit damage imposed after transplanting, in a 30% level of soil water retention capacity.
Keywords: Abiotic stress; Beneficial element; Leaf spraying; Plant nutrition; Polymerization; Saccharum officinarum L